Effect of Pruning on Yield of Sunflower in Albizia lebbeck based Agri-silvi System - Joseph, B.; Rao, L.G.Giri; Sreemannarayana, B. (Indian Journal of Agroforestry, 2020)
An experiment was initiated during Kharif ’93 and continued upto 1997 to study the effect of pruning practices in Albizia lebbeck and their influence on the yield of sunflower crop grown in a rainfed Alfisol. Results revealed that during first year of experimentation, there was no significant yield loss in sunflower crop due to tree component. However, during second, third and fourth years, the narrow spacing (4 x 4 m) adopted for trees had significant negative influence on crop growth. The results also proved that due to pollarding of trees at a height of 1.5 m from the ground, the negative impact of trees could be avoided and sustainable advantage can be derived from A. lebbeck based agri-silvi system. The yield reduction of 20 per cent occurred due to tree interference could well be compensated by value realised (Rs. 1808) from pollarded portions (36.15 q/ha). Though the benefit-cost ratio (2.68) was marginally high with pure crop, as compared to the ratio (2.40) obtained in treatment of tree pollarding. In view of indirect benefits provided by the trees, the B:C ratio of 2.40 can be rated as high.